Properties of DNA complexes with new cationic surfactants - Hebda, Edyta; Niziol, Jacek; Pielichowski, Jan; Sniechowski, Maciek; Jancia, Malgorzata (Publishing House of Lviv Polytechnic National University, 2011)
In this paper properties of deoxyribonucleic acid (DNA) complexes with originally proposed cationic surfactants are described. Properties of prepared complexes were studied with the help of UV-vis-NIR and FT-IR spectroscopies, TGA and DSC analysis and X-ray diffractometry. These complexes are intended for future applications in organic electronics. Описані властивості комплексів дезоксирибонуклеїнової кислоти (ДНК) з новими катіонними поверхнево-активними речовинами. За допомогою UV-vis-NIR і ІЧ-Фур'є спектроскопії, ТГА і ДСК аналізу та рентгенівської дифрактометрії вивчено властивості розроблених комплексів. Показано можливість використання таких комплексів в органічній електроніці.
Властивості комплексів ДНК з новими катіонними пар
Keywords: DNA; DNA complex; natural polymers; ДНК; комплекс ДНК; природні полімери